2010
DOI: 10.1007/s00464-010-1459-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic left lateral liver resection should be a standard operation

Abstract: Although no randomized controlled trials have compared open and laparoscopic liver resection, this metaanalysis demonstrated that laparoscopic left lateral resection is a safe and feasible option associated with a reduced overall complication rate. The authors conclude that it should be performed routinely in liver centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 9 publications
0
29
0
6
Order By: Relevance
“…Increasing numbers of authors have reported promising results with LH which is associated with decreased blood loss and hospital stay without compromising on oncologic outcomes [10][11][12][13]. Presently, some experts have even proposed that LH should be the standard approach for certain liver resections such as left lateral sectionectomies [14].…”
Section: Introductionmentioning
confidence: 97%
“…Increasing numbers of authors have reported promising results with LH which is associated with decreased blood loss and hospital stay without compromising on oncologic outcomes [10][11][12][13]. Presently, some experts have even proposed that LH should be the standard approach for certain liver resections such as left lateral sectionectomies [14].…”
Section: Introductionmentioning
confidence: 97%
“…In the authors experience laparoscopic left lateral resection can be performed as quick laparoscopically as open once the learning curve has been overcome. Transection time can be less than 1 hour as reported in a recent meta-analysis 59 . For major hepatectomy operative times are prolonged and the duration of anaesthesia can be in excess of 5 hours compared to 3 hours for open surgery 60 61 .…”
Section: Wwwintechopencommentioning
confidence: 79%
“…Without randomized studies this will be difficult to confirm as laparoscopic enthusiasts may have a tendency to send patients home earlier than usual practise and may vary between centres. Generally the disadvantage of higher costs is offset by the shorter stay 88,7,89,90 .…”
Section: The Learning Curve/patient Benefitmentioning
confidence: 99%
“…Furthermore, these were found to be lower after LLR in 40 and 11 studies, respectively. Twelve meta-analyses and one Cochrane report were also analyzed [35][36][37][38][39][40][41][42][43][44][45][46][47] and consistent results included reduced blood loss and transfusions requirements when studied. This clearly shows that, in selected patients LLR when compared with open surgery is associated with reduced blood loss and subsequent transfusion rates.…”
Section: Discussionmentioning
confidence: 99%